Trauma and emergency nurse specialists’ perceptions of factors that hinder and facilitate the implementation of specialised skills in their practice within the public health sector in the Western Cape Province - Stevens, Haroldene (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNur)--Stellenbosch University, 2021.